(untitled) (Journal of the College of Basic Education, 2024)
Classroom management refers to how instructors could organize their classrooms and student interactions to keep students interested, eliminate distractions, and promote learning. The current study aims to finding out the classroom management techniques most frequently used by EFL college instructors according to their frequencies and discovering the influence of classroom management on the teaching/learning process used by university instructors. The sample of the current study is 40 instructors from University of Baghdad. After determining the questionnaire’s validity and reliability, it is administered to the sample. The results indicate that instructors utilized classroom management techniques with a weighted mean score greater than (3). This demonstrates that university English instructors have successfully employed classroom management to teach the English language. In light of the findings, some conclusions and recommendations are provided.